Evaluation of medicine package inserts: a study of two cases of Pelargonium sidoides D.C. phytomedicines - Tiago Duarte Linhares; Danilo Ribeiro de Oliveira; Michele Feitoza Silva (Universidade de São Paulo, 2010)
In order for a phytotherapeutic drug be approved and sold in Brazil, it must be registered with the National Sanitary Surveillance Agency (ANVISA), where the quality, safety and efficacy of the product are carefully appraised. In addition, the drug must also meet a number of criteria one of which is the adequacy of the package inserts. Therefore, the aim of this study was to appraise the package inserts of all phytotherapeutic drugs produced using a standardized extract of Pelargonium sidoides, which were registered and available from Brazilian pharmacies. This checking was to ascertain whether these inserts fulfilled the requirements stipulated by RDC 140/03. The information required under RDC 140/03 was appraised through a previously devised standard form. Evaluation of the package inserts revealed that neither of the two brands fully met the requirements of the legislation. Manufacturer 'A' met only 37.0% of the requirements satisfactorily, while 16.0% of the information was considered unsatisfactory and 47.0% of the information was absent. Regarding manufacturer 'B', 64.2% of the analyzed requirements were considered satisfactory, while 16.0% were considered unsatisfactory and 19.8% of the information was absent. A package insert should contain information about medicine for consumers, pharmacists and doctors. However, the results obtained in this study showed that the information presented in the package insert of both medicines was unsatisfactory, and in many cases, violates the legislation. Para que um medicamento fitoterápico seja comercializado no Brasil, este deve ser registrado junto à ANVISA, onde são avaliados todos os aspectos referentes à qualidade, segurança e eficácia do produto, além de verificar se estes atendem alguns requisitos, sendo um deles a adequação da bula. Por esta razão, neste estudo foram avaliadas as bulas de todos os fitoterápicos elaborados à base do extrato padronizado de Pelargonium sidoides, registrados e disponíveis no mercado brasileiro, com o intuito de verificar se estas atendem aos requisitos exigidos pela RDC 140/03. No presente trabalho, as informações exigidas pela RDC 140/03 foram avaliadas através de um formulário padrão previamente elaborado. Após avaliação das bulas pode ser verificado que nenhuma das duas marcas atendia por completo as exigências da legislação, sendo que o fabricante "A" atendeu apenas 37,0% dos requisitos exigidos de forma satisfatória, enquanto 16,0% das informações foram consideradas insatisfatórias e em 47,0% as informações estavam ausentes. Com relação ao fabricante "B", 64,2% dos itens analisados foram considerados satisfatórios, enquanto 16,0% foram considerados insatisfatório e em 19,8% as informações estavam ausentes. A bula deveria conter informações sobre o medicamento para consumidores, farmacêuticos e médicos, no entanto, os resultados obtidos neste estudo mostram que as informações apresentadas nas bulas foram insatisfatórias, e em muitos casos, violavam a legislação vigente.